Leadership behaviour, entrepreneurial orientation and organisational performance in Malaysian small and medium enterprises - Azizah Hashim (Tanjong Malim, 2019)
Leadership behaviour, entrepreneurial orientation and organisational performance in Malaysian small and medium enterprises by Azizah Hashim